A randomized controlled trial of the effectiveness of handheld computers for improving everyday memory functioning in patients with memory impairments after acquired brain injury. (May 2014) - Lannin, Natasha; Carr, Belinda; Allaous, Jeanine; Mackenzie, Bronwyn; Falcon, Alex; Tate, Robyn
Objective: To determine the effectiveness of personal digital assistant devices on achievement of memory and organization goals in patients with poor memory after acquired brain injury. Design: Assessor blinded randomized controlled trial. Setting: Specialist brain injury rehabilitation hospital (inpatients and outpatients). Participants: Adults with acquired brain impairments (85% traumatic brain injury; aged ≥17 years) who were assessed as having functional memory impairment on the Rivermead Behavioural Memory Test (General Memory Index). Interventions: Training and support to use a personal digital assistant for eight weeks to compensate for memory failures by an occupational therapist. The control intervention was standard rehabilitation, including use of non-electronic memory aids. Main outcome measures: Goal Attainment Scale which assessed achievement of participants' daily memory functioning goals and caregiver perception of memory functioning; and General Frequency of Forgetting subscale of the Memory Functioning Questionnaire administered at baseline (pre-randomization) and post intervention (eight weeks later). Results: Forty-two participants with memory impairment were recruited. Use of a personal digital assistant led to greater achievement of functional memory goals (mean difference 1.6 (95% confidence interval (CI) 1.0 to 2.2), P = 0.0001) and improvement on the General Frequency of Forgetting subscale (mean difference 12.5 (95% CI 2.0 to 22.9), P = 0.021). Conclusions: Occupational therapy training in the use of a handheld computer improved patients' daily memory function more than standard rehabilitation.